A Case Study on Agile Estimating and Planning using Scrum - Mahnic, V. (Elektronika ir Elektrotechnika, 2011)
We describe a case study that was conducted at the University of Ljubljana with the aim of studying the behavior of development teams using Scrum for the first time, i.e., a situation typical for software companies trying to introduce Scrum into their development process. 13 student teams were required to develop an almost real project strictly using Scrum. The data on project management activities were collected in order to measure the amount of work completed, compliance with the release and iteration plans, and ability of effort estimation, thus contributing to evidence-based assessment of the typical Scrum processes. It was found that the initial plans and effort estimates were over-optimistic, but the abilities of estimating and planning improved from Sprint to Sprint. Most teams were able to define almost accurate Sprint plans after three Sprints. In the third Sprint the velocity stabilized and the actual achievement almost completely matched the plan. Bibl. 25, tabl. 4 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.372